2013
DOI: 10.3389/fmicb.2013.00078
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Fungal Community Composition in Response to Elevated Atmospheric CO2 and Nitrogen Fertilization Varies with Soil Horizon

Abstract: Increasing levels of atmospheric carbon dioxide (CO2) and rates of nitrogen (N)-deposition to forest ecosystems are predicted to alter the structure and function of soil fungal communities, but the spatially heterogeneous distribution of soil fungi has hampered investigations aimed at understanding such impacts. We hypothesized that soil physical and chemical properties and fungal community composition would be differentially impacted by elevated atmospheric CO2 (eCO2) and N-fertilization in spatially separate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

15
84
8
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(109 citation statements)
references
References 72 publications
15
84
8
2
Order By: Relevance
“…Interestingly, decreased and increased overall relative abundances of Ascomycota and Basidiomycota in eCO 2 samples were observed for the 119 OTU. Compared to the recent study in a forest FACE site by Weber et al (31), our results were generally consistent that eCO 2 had no significant effects on high-level fungal groups when relative abundances for all OTU were considered. Our results were also consistent with a previous study that the fungal richness was not significantly affected by eCO 2 (57).…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Interestingly, decreased and increased overall relative abundances of Ascomycota and Basidiomycota in eCO 2 samples were observed for the 119 OTU. Compared to the recent study in a forest FACE site by Weber et al (31), our results were generally consistent that eCO 2 had no significant effects on high-level fungal groups when relative abundances for all OTU were considered. Our results were also consistent with a previous study that the fungal richness was not significantly affected by eCO 2 (57).…”
Section: Discussionsupporting
confidence: 73%
“…The grassland soil ecosystem in the BioCON experimental site in Minnesota was dominated by Ascomycota (81% at aCO 2 and 77% at eCO 2 ) and Basidiomycota (11% at aCO 2 and 14% at eCO 2 ). Compared to the reports by previous studies (31,(58)(59)(60)(61), fungal community composition in soil varied greatly across different types of soil ecosystems. Such variations in fungal community composition between different studies might be caused by different coverage of different primer sets or phylogenetic markers (such as ITS versus 28S) (62), but more likely caused by plant species, soil, and/or climate differences (58).…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…For instance, drought reduced the relative abundance of Proteobacteria in our study, as previously reported in a constructed old-field ecosystem (Castro et al, 2010); two abundant Proteobacteria OTUs (Methylobacterium 2 and Mitsuaria) had a significantly lower relative abundance in the drought treatment. In contrast, Weber et al (2013) reported a positive response of Ascomycetes to nitrogen addition, whereas many of the abundant Ascomycete OTUs decreased in relative abundance in our nitrogen treatment. Also, in contrast to prior studies, added nitrogen or drought did not increase the relative abundance of Actinobacteria (Ramirez et al, 2012;Barnard et al, 2013).…”
Section: Discussioncontrasting
confidence: 40%
“…Broadly speaking, the taxonomic composition observed in this study is similar to that found in other terrestrial litter and soil systems. The majority of fungal sequences in this study were Ascomycota and Basidiomycota (Barnard et al, 2013;Voriskova and Baldrian, 2013;Weber et al, 2013), and Proteobacteria, Bacteriodetes and Actinobacteria made up most of the bacterial diversity (Castro et al, 2010;Sheik et al, 2011;Barnard et al, 2013;Kim et al, 2014). In contrast, many soils contain a large fraction of Acidobacteria (Castro et al, 2010;Sheik et al, 2011;Barnard et al, 2013;Kim et al, 2014), but they represented o1% of our litter communities.…”
Section: Discussionmentioning
confidence: 94%